UPAYA GURU AKIDAH AKHLAK DALAM MEMBENTUK PERILAKU TAAT KEPADA ORANG TUA DI MTS RAUDATUL MUTA’ALIMIN 1 SUMBERBARU JEMBER - As’adur Rofiq; Misbahul Munir (Journal Islamic Studies, 2022)
This research examines the efforts and factors supporting and inhibiting Akidah Akhlak teachers in shaping obedient behavior to parents at MTs Raudlatul Muta'allimin 1 Sumberbaru Jember. Qualitative approach with field research design. The research instrument used observation, interviews with the principal, Akidah Akhlak teachers and students, and documentation. The results of this research are Akidah Akhlak teachers using three methods, namely the method of advice, example and habituation. The supporting factors for the teacher of Akidah Akhlak. The internal factor is the motivation within the students. External factors, a). Environment. b). presence of LKS. c). habit. While the inhibiting factor for the teacher is Akidah Akhlak. The internal factor is the absence of student motivation. External factors a). busy and forget parents. b). family and community environment. c). technological developments that have a negative impact on students.